Finding the Correct Pesticide Applicator License in Florida - Erin E. Harlow; Luke B. Harlow; Susan Haddock; Brett Bultemeier (EDIS)
It can be difficult to determine which pesticide license is needed for an applicator's specific situation. Each license has unique study material, a different fee structure, and varied CEU requirements. This new 71-page publication utilizes a "dichotomous key" for the pesticide license process to help guide users to the correct license. Each license category page will also provide all the relevant information needed to get and maintain a license in the state of Florida. https://edis.ifas.ufl.edu/pi292